2018
DOI: 10.1002/er.4000
|View full text |Cite
|
Sign up to set email alerts
|

Improving indoor thermal comfort by using phase change materials: A review

Abstract: Summary Phase change materials (PCMs) have great potentials to be used in modern building materials to stabilize indoor temperature fluctuations for improving thermal comfort. This paper presents a comprehensive review on the use of PCMs in buildings to improve thermal comfort without increasing energy consumption. Concise discussions of the experimental and computational works reported in literature are presented. A special focus of this review is devoted to discussing different analysis methods and models us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 107 publications
(168 reference statements)
0
52
0
Order By: Relevance
“…1 As promising energy storage materials, phase-change materials (PCMs) have been a deep concern of academic circles in recent years. [5][6][7] PCMs could be classified as organic and inorganic PCMs. [5][6][7] PCMs could be classified as organic and inorganic PCMs.…”
Section: Introductionmentioning
confidence: 99%
“…1 As promising energy storage materials, phase-change materials (PCMs) have been a deep concern of academic circles in recent years. [5][6][7] PCMs could be classified as organic and inorganic PCMs. [5][6][7] PCMs could be classified as organic and inorganic PCMs.…”
Section: Introductionmentioning
confidence: 99%
“…1 A proper PCM for building applications should meet a number of criteria related to the desired thermophysical, kinetic, and chemical properties as well as economics. 4 Metal salts and hydrated salts are examples of inorganic PCMs while organic PCMs include paraffin and nonparaffin compounds. 2,3 They should also have a melting temperature slightly above 20°C to meet the need of thermal comfort of the building.…”
Section: Introductionmentioning
confidence: 99%
“…Chai 7 studied the bifunctional microencapsulated n-eicosane for various applications, such as waste heat recovery and treatment, intelligent textiles and medical protective clothing, and food preservation. Abuelnuor 19 found that PCMs have great potentials to be used in modern building materials to stabilize indoor temperature fluctuations for improving thermal comfort. Sari 9 considered magnetic refrigeration a serious alternative system for food preservation.…”
Section: Introductionmentioning
confidence: 99%